Kajian Perbandingan Asesmen Green Building Bangunan Gedung Baru Menggunakan Sistem Greenship New Building Versi 1.2 dan Versi 2.0 - WINDU NUR AZZUKHRUF SIADARI; Erizal; Yudi Chadirin (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
Climate change is a problem that becomes an environmental issue in every government. Increased awareness of environmental issues has made green building construction an industry that has made many improvements to be more environmentally friendly. Green building construction in Indonesia can only be certified greenship new building version 1.2 issued by Green Building Council Indonesia (GBCI). This research relates to the grenship new building which underwent a change from greenship new building version 1.2 to version 2.0 in 2019. Meanwhile, this study uses comparative and qualitative methods in discussing assessment points in greenship new building. The results of the study explained that there were additional points for the assessment criteria with 2%-3% weighted values increased from the previous criteria.